Effects of polyimide curing on image sticking behaviors of flexible displays - Hyojung Kim (Nature Portfolio, 2021)
Abstract Flexible displays on a polyimide (PI) substrate are widely regarded as a promising next-generation display technology due to their versatility in various applications. Among other bendable materials used as display panel substrates, PI is especially suitable for flexible displays for its high glass transition temperature and low coefficient of thermal expansion. PI cured under various temperatures (260 °C, 360 °C, and 460 °C) was implemented in metal–insulator–metal (MIM) capacitors, amorphous indium gallium zinc oxide (a-IGZO) thin-film transistors (TFT), and actual display panels to analyze device stability and panel product characteristics. Through electrical analysis of the MIM capacitor, it was confirmed that the charging effect in the PI substrates intensified as the PI curing temperature increased. The threshold voltage shift (ΔVth) of the samples was found to increase with rising curing temperature under negative bias temperature stress (NBTS) due to the charging effect. Our analyses also show that increasing ΔVth exacerbates the image sticking phenomenon observed in display panels. These findings ultimately present a direct correlation between the curing temperature of polyimide substrates and the panel image sticking phenomenon, which could provide an insight into the improvement of future PI-substrate-based displays.